1993
DOI: 10.1002/zamm.19930730207
|View full text |Cite
|
Sign up to set email alerts
|

Creeping Flow Past a Porous Spherical Shell

Abstract: An exact solution for the creeping flow past a porous spherical shell has been obtained using the Stokes & Brinkman equations. Expressions for the velocities and pressure fields both inside and outside of porous spherical shell are obtained and the force acting on the shell is also determined. It is found that the drag on a porous spherical shell is smaller as compared to the shell with solid core. Several limiting cases of the solution are also discussed. In particular it is shown that the solution obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…this result agrees with a well-known result earlier reported by Brinkman (1947), Ooms et al (1970), Neale et al (1973), Masliyah et al (1987), Qin and Kaloni (1988), Qin and Kaloni (1993), Vasin and Kharitonova (2011a), Vasin and Kharitonova (2011b) and later Yadav and Deo (2012) for the drag force experienced by a permeable sphere in an unbounded clear fluid.…”
Section: Resultssupporting
confidence: 93%
“…this result agrees with a well-known result earlier reported by Brinkman (1947), Ooms et al (1970), Neale et al (1973), Masliyah et al (1987), Qin and Kaloni (1988), Qin and Kaloni (1993), Vasin and Kharitonova (2011a), Vasin and Kharitonova (2011b) and later Yadav and Deo (2012) for the drag force experienced by a permeable sphere in an unbounded clear fluid.…”
Section: Resultssupporting
confidence: 93%
“…Payne and Straughan [17] have shown that the solution to thermal flow problems depends continuously on the parameter α when Darcy's law is adopted in the porous medium and Stokes's flow holds in the fluid layer. Indeed, the Beavers-Joseph condition has proved successful in other slow-flow situations, such as flow past a porous sphere (see Qin and Kaloni [18]). However, the analysis of [17] casts serious doubt on whether (1.2) would be realistic for larger fluid velocities for which Navier-Stokes flow is valid.…”
Section: Introductionmentioning
confidence: 98%
“…The problem of creeping flow past a porous particle in terms of Brinkman's equation has been firstly treated by Higdon and Kojima [13], by using a direct boundary integral approach. Qin and Kaloni [33] used the Stokes and Brinkman equations for the Stokes flow past a porous spherical shell, and derived an explicit solution. Davis and Stone [5] studied the flow within and around a porous particle which is contained in a bed of many similar particles, and used two approximate models based on the Brinkman equations in order to describe the principal features of the flow.…”
Section: Introductionmentioning
confidence: 99%